Autocuidado de pessoas idosas com Diabetes Mellitus e a relação interpessoal enfermeiro-paciente - Ferreira, Gerlania Rodrigues Salviano (2020)
Introduction: Diabetes mellitus is a chronic condition that has stood out due to its high incidence and prevalence. Complications related to the disease offer serious risks to the health of individuals, which can be avoided and / or mitigated by performing self-care practices. For this, the professional, especially the nurse, must provide security, trust, welcoming and humanization to the patient through effective interpersonal relationships, which favors complicity in formulating strategies for better adherence to the therapeutic plan. Objective: To evaluate the self-care of elderly people with diabetes mellitus and the nurse-patient interpersonal relationship. Method: exploratory and descriptive, cross-sectional study, with a quantitative approach, carried out with 144 elderly people with diabetes mellitus registered in the Basic Health Units of the city of João Pessoa, Paraíba, Brazil, between the months of June to October 2019. data were collected by interviewing patients in the waiting room, in social groups and at home. An instrument was used to obtain data regarding the sociodemographic profile, health conditions, characteristics of the disease and assistance received, the Questionnaire on Self-Care Activities with Diabetes and the Questionnaire on interpersonal relationships in nursing care. The analysis was performed using descriptive and inferential statistics. The project was approved under opinion No. 3,411,237. Results: elderly people with diabetes presented greater adherence to self-care activities in items related to taking insulin injections as recommended; take diabetes medicines as recommended and take the indicated number of diabetes tablets. Self-care was significantly associated with some variables of sociodemographic characteristics, health conditions, disease characteristics and care received Interpersonal relationships in nursing care presented a moderate level of effectiveness. Significantly associated with the variables personal income, presence of comorbidity, systemic arterial hypertension and use of oral hypoglycemic agents, insulin and antihypertensives. The correlation between the two scales was significant, and it was evidenced that the effectiveness of the interpersonal relationship in nursing care for patients with diabetes provided greater adherence to self-care practices. Conclusions: the effective interpersonal relationship of the nurse-patient significantly influences the modification of self-care practices in diabetes mellitus. As it is one of the first studies to measure the interpersonal relationship in nursing care, it is considered essential that further research is carried out in different regions and populations, in order to support these findings and provide improvement in nursing care.